What Is the Relationship Between Hippocampal Neurogenesis Across Different Stages of the Lifespan? - Bond, Allison M.; Ming, Guo-li; Song, Hongjun (Frontiers in Neuroscience, 2022)
Hippocampal neurogenesis has typically been studied during embryonic development or in adulthood, promoting the perception of two distinct phenomena. We propose a perspective that hippocampal neurogenesis in the mammalian brain is a continuous, lifelong developmental process. We summarize the common features of hippocampal neurogenesis that are maintained across the lifespan, as well as dynamic age-dependent properties. We highlight that while the progression of hippocampal neurogenesis across the lifespan is conserved between mammalian species, the timing of this progression is species-dependent. Finally, we discuss some current challenges in the hippocampus neurogenesis field, and future research directions to address them, such as time course analysis across the lifespan, mechanisms regulating neurogenesis progression, and interspecies comparisons. We hope that this new perspective of hippocampal neurogenesis will prompt fresh insight into previous research and inspire new research directions to advance the field to identify biologically significant ways to harness the endogenous capacity for neurogenesis in the hippocampus.